What s in a word? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
What s in a word?The English word library probably comes from the Latin term libraria for shop, from the time when books were sold, not lent, in bookstores. The French and Portuguese words for bookstore are, to this day, librairie and...